Distributional patterns of two sympatric blue crabs (Callinectes) and the implications for conservation management at the South-west Atlantic subtropical shelf - Herrera, Daphine Ramiro [UNESP]; Costa, Rogerio Caetano da [UNESP] (Taylor & Francis, 2022)
Changes in species distribution patterns allow managers to monitor the conservation status of species. This study investigated the distribution and segregation in the blue crabs Callinectes danae and Callinectes ornatus in the South-west Atlantic subtropical shelf. We characterized the crabs’ abundance and related it to environmental factors. Abundance expressed as catch per unit effort estimates deviated significantly from crabs’ abundances assessed by years: in Year 1, station S7 showed the highest abundance for C. danae and the lowest for C. ornatus. In Year 2, the abundance of species only differed significantly in station S2. Summer was the season with the highest abundance of C. danae and spring of C. ornatus. Temperature was the environmental factor that modulated the distribution of blue crabs. The crabs presented different spatial and temporal distribution patterns, although there was no evident segregation between species. This ecological study indicates a potential site in the South-west Atlantic subtropical shelf to maintain the reproductive viability of the population.
Keywords: Brachyura; environmental factors; spatio-temporal distribution; swimming crabs